From Platelet-Rich Plasma to Advanced Platelet-Rich Fibrin: Biological Achievements and Clinical Advances in Modern Surgery - Caruana, Andrea; Savina, Daniele; Macedo, José Paulo; Soares, Sandra Clara (European Journal of Dentistry, 2019)
In the past 20 years, the platelet concentrates have evolved from first-generation products, i.e., platelet-rich plasma (PRP) and plasma rich in growth factors to the second-generation products such as leukocyte-platelet-rich fibrin (L-PRF) and advanced platelet-rich fibrin (A-PRF). These autologous products with a higher leukocyte inclusion and flexible fibrin mesh act as a scaffold to increase cellular migration in the angiogenic, osteogenic, and antimicrobial potential of these biomaterials in tissue regeneration. In the second-generation platelet concentrates, the protocols are easier, cheaper, and faster with an entire physiological fibrin matrix, resulting in a tridimensional mesh, not as rigid as one of the first generations. This allows the slow release of molecules over a longer period of time and triggers the healing and regenerative process at the site of injury. The potential of A-PRF to mimic the physiology and immunology of wound healing is also due to the high concentration of growth factors released as follows: vascular endothelial growth factor, platelet-derived growth factor, transforming growth factor-β, and anti-inflammatory cytokines that stimulate tissue cicatrization, vessels formation, and bone cell proliferation and differentiation. Furthermore, the number of neutrophils and monocytes/macrophages is higher releasing important chemotactic molecules such as chemokine ligand-5 and eotaxin. Thus, L-PRF and A-PRF have been used, especially in implantology, periodontology, and maxillofacial surgery. Future clinical applications include tissue regeneration/grafts, ulcers/skin necrosis in the diabetic patient and others, plastic surgery, and even musculoskeletal lesions.
Keywords: advanced platelet-rich fibrin; fibrin; plasma rich in growth factors; platelet concentrates; platelet growth factors; platelet-rich fibrin; platelet-rich plasma; tissue regeneration